1973
DOI: 10.1128/aem.25.1.111-114.1973
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Partial Characterization of a Mycotoxin from Penicillium roqueforti

Abstract: Extracts of pure cultures of Penicillium roqueforti isolated from toxic feed samples and of P. roqueforti NRRL 849 were lethal to rats by either intraperitoneal or oral administration. Purification studies guided by this test led to the isolation of a major toxin which showed intraperitoneal and oral median lethal dose values in weanling rats of 11 and 115 mg/kg, respectively. Partial characterization of the crystalline compound, C 17H2006, by infrared, ultraviolet, PMR, and mass spectroscopy, and by several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
7

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 0 publications
0
36
0
7
Order By: Relevance
“…The very low distribution half-life of OTC (6 min) compared to that of OTA (160 min) suggests that esterification of OTA facilitated its penetration in cell, which in turn affects maximal tissue concentrations and overall toxicity. OTC is extremely toxic to animals, such as pig, poultry [464] and dairy cattle [467]. In cell culture it has been recently demonstrated that OTC is more toxic than OTA [468,469].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…The very low distribution half-life of OTC (6 min) compared to that of OTA (160 min) suggests that esterification of OTA facilitated its penetration in cell, which in turn affects maximal tissue concentrations and overall toxicity. OTC is extremely toxic to animals, such as pig, poultry [464] and dairy cattle [467]. In cell culture it has been recently demonstrated that OTC is more toxic than OTA [468,469].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…It is well known that Penicillium roqueforti is the principal fungus isolated from mouldy silage. Some toxic metabolites such as PR toxin were reported from P roqueforti isolated from mouldy silage (Wei et al 1973). In this paper, the authors report on indole alkaloids and roquefortines from P roqueforti isolated from moulded maize silage.…”
Section: Discussionmentioning
confidence: 93%
“…A toxic metabolite, fumigaclavine C, was found in the culture broth of A fumigatus isolated from maize silage (Cole et al 1977) and is structurally very similar to roquefortine A. Wei et al (1973) produced PR-toxin from isolates of Penicillium roqueforti obtained from mouldy silage.…”
Section: Storage Derived Mycotoxinsmentioning
confidence: 99%